Autocrine growth stimulation of a human T-cell lymphoma line by interleukin 2. - Duprez, V (1985)
The ability of tumor cells to produce and to respond to their own growth factor (autocrine secretion) may be of importance for their growth. We describe a human tumor cell line regulated by an autocrine secretion of the growth factor interleukin 2 (IL-2). This T-lymphocyte cell line, IARC 301, was established from a patient with a T-cell lymphoma in the absence of any added specific growth factor. It constitutively expresses biologically functional high-affinity cell-surface receptors for IL-2 as shown by the binding of both radiolabeled purified IL-2 and monoclonal antibodies to IL-2 receptors. In addition, it synthesizes IL-2, which is bound to cell surface receptors. Monoclonal antibodies directed against either IL-2 or the IL-2 receptor block IARC 301 cell growth. These findings demonstrate that the proliferation of this tumor cell line is mediated by an autocrine pathway involving endogenous IL-2 production and its binding to cell surface receptors.